The role of loneliness in the development of depressive symptoms among partnered dementia caregivers: Evidence from the English Longitudinal Study of Aging. Issue 1 (26th March 2021) - Saadi, J. P.; Carr, E.; Fleischmann, M.; Murray, E.; Head, J.; Steptoe, A.; Hackett, R. A.; Xue, B.; Cadar, D.
Abstract: Background: Depressive symptoms are highly prevalent among partnered dementia caregivers, but the mechanisms are unclear. This study examined the mediating role of loneliness in the association between dementia and other types of care on subsequent depressive symptoms. Methods: Prospective data from partnered caregivers were drawn from the English Longitudinal Study of Aging. The sample consisted of 4, 672 partnered adults aged 50–70 living in England and Wales, followed up between 2006–2007 and 2014–2015. Caregiving was assessed across waves 3 (2006–2007), 4 (2008–2009), and 5 (2010–2011), loneliness at wave 6 (2012–2013), and subsequent depressive symptoms at wave 7 (2014–15). Multivariable logistic regression models were used to assess the association between caregiving for dementia and depressive symptoms compared to caregiving for other illnesses (e.g., diabetes, coronary heart disease (CHD), cancer, and stroke). Binary mediation analysis was used to estimate the indirect effects of caregiving on depressive symptoms via loneliness. Results: Care for a partner with dementia was associated with higher odds of depressive symptoms at follow-up compared to those not caring for a partner at all (odds ratio [OR] = 2.6, 95% confidence intervals [CI]: 1.4, 5.1). This association was partially mediated by loneliness (34%). Care for a partner with other conditions was also associated with higher odds of depressive symptoms compared to non-caregiving partners (OR = 1.7, 95% CI: 1.2, 2.5), but there was no evidence of an indirect pathway via loneliness. Conclusion: Loneliness represents an important contributor to the relationship between dementia caregiving and subsequent depressive symptoms; therefore, interventions to reduce loneliness among partnered dementia caregivers should be considered.